1982
DOI: 10.1037/0022-0663.74.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Writing and revising persuasive documents: Cognitive demands.

Abstract: In two experiments, college students wrote preliminary and final drafts of a persuasive document. In Experiment 1, the need for writers to comply with mechanics (i.e., punctuation and spelling), to form complete sentences, and to sequence their ideas, respectively, were eliminated one at a time from preliminary-draft formats. The elimination of sentence-formation and sequence operations produced corresponding increments in persuasive argument production. In Experiment 2, writers with average verbal ability ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 13 publications
3
42
2
1
Order By: Relevance
“…Hayes and Berninger (2010) found that children in Grades 2, 4 and 6 produced more ideas in a dictation task, which has no transcription requirements, than in a similar writing task. Moreover, Glynn, Britton, Muth, and Dogan (1982) found that college students instructed to ignore punctuation and spelling during planning produced more arguments than those instructed to attend to these mechanical aspects.…”
Section: Transcription Constrains Planning and Translatingmentioning
confidence: 99%
“…Hayes and Berninger (2010) found that children in Grades 2, 4 and 6 produced more ideas in a dictation task, which has no transcription requirements, than in a similar writing task. Moreover, Glynn, Britton, Muth, and Dogan (1982) found that college students instructed to ignore punctuation and spelling during planning produced more arguments than those instructed to attend to these mechanical aspects.…”
Section: Transcription Constrains Planning and Translatingmentioning
confidence: 99%
“…Most studies show that using an outline strategy positively impacts writing performance and leads to increased text quality (Erkens, Kanselaar, Prangsma, & Jaspers, 2002;Galbraith et al, 2005;Glynn, Britton, Muth, & Dogan, 1982;Kellogg, 1987Kellogg, , 1988Kellogg, , 1990Kozma, 1991). In addition, outlining may decrease mental effort expended during writing.…”
Section: Effects Of Outliningmentioning
confidence: 99%
“…Glynn et al, 1982). The writing tasks were given by means of a written instruction which was equivalent for the two conditions (i.e., with and without outline tool) except for the specific requirement to use the outline tool.…”
Section: Writing Tasksmentioning
confidence: 99%
“…In such cases, the participant may have only a small margin in allocating his or her resources to each of the three tasks and does so on the basis ofa subjective evaluation of the experimenter's demands (cf. the notion of "cognitive balance" in Glynn, Britton, Muth, & Dogan, 1982).…”
Section: Training Of the Directed Retrospectionmentioning
confidence: 99%